PERBANDINGAN PRESTASI MAHASISWA DARI SISTEM SELEKSI PENERlMAAN MAHASISWA BARU JALUR PMDP DAN JALUR UJI TULIS POLTEKKES KEMENKES SURABAYA - Marlik .; AT Diana; Sudjarwo . (Poltekkes Kemenkes Surabaya, 2015)
Third Diploma (DIU) vocational education of Poltekkes Kemenkes Surabaya graduates medical healthofficer who are ready to work, therefore of candidates of new students are qualified prudently throughInvestigation Of Interest And Aptitude (PMDP) system (2010 - 2013) which expecting to obtain potentialcandidate of new students who have stable achievement, also through Written Test (UTUL) system whichexpecting to obtain candidates of new students who are appropriate to the determined standard in orderto be a student who Is able to get achievement, follow the studying process properly , and graduatecompetently. The first data shows an average Academic Achievement Index (IP) of first semester fromPMDP system on ProdI DIll of Environmental Health Is 2.995, (2.S8 - 3.79) while average [P of UTUlsystem students Is 3.16 (2.37- 3.68). How about the result of the other Prodi D III, Does the samecondition occur?Therefore a research has been executed to compare the academic achievements of students in PoltekkesKemenkes Surabaya, observed from PMDP system and UTUL system on 2011, 2012 and 2013 which thedesign is Deoiptive Explorative. Variable of the research are active students who follow all activities ofstudying process on 2013/2014 academic year and also their academic achievement (cumulative IP) , thenthe data was analyzed descriptively.Results of research show that from 2.650 active students, consists of 2.278 students (86%) were acceptedthrough UTUL system, almost all students are female (2213 students I 83%). Observed from the highschool they were graduated from, PMDP system students who are from Senior High School (SMA) is 14%(310 students) and UTUL system is 86% (1.967 students ), whereas high school status, students who arefrom state high school is 13% (258 students) from PMDP system and 87% (2.031 students) from UTULsystem.Academic achievements of Poltekkes Kemenkes Surabaya's students show the average of IPK (CumulativeIP) is 2,94 - 3,00. The comparative analysis shows the range of IPK of all students from all Prodi D III,that is 1,38-3,96 (from PMDP) and 1,77-3,86 (from UTUL). If we compare the average of the highest IPKand the maximum IPK shows that most of it comes from PMDP (74% and 52%). And the analysis of theorigin of high school shows that the highest average of IPK comes from Senior high School (SMA) PMDPexcept Health Nutrition (Islamic Senior High School (MA) UTUL) , Sidoarjo Nursing (UTUL SMA), BangkalanMidwifery (PMDP SMA), and 8ectromedical Enggineering (MA UTUL). And the analysis of school's statusshows that most of the average of the highest IPK comes from State school PMDP except Health Nutrition(Private school PMDP),Sidoarjo Nursing and Bangkalan Midwifery (State school UTUL).Based on the results, therefore advlces to the new student's admissions system of Poltekes KemenkesSurabaya are must increase the number of male new students especially in Environmental Health major asthe market or the employers demands that sometimes hinted male, PMDP system must be maintained butstill consider the requirements of the higher grades in senior high school ( 8.0) and 40% proportion ofnew students from PMDP is quite appropriate in order to get better IP with narrower distribution. UTUlsystem considers UTUL score determinateness / minimal score, not only based on rank. If possible tomaintain candidates of new students whose score is appropriate by opening second admission and secondoption. Particularly to students who are from Vocational High School (SMK) or Social Concentration ofSenior High School (SMA IPS) need to be given a matriculation